The Myth of Representations of Africa: A comprehensive scoping review of the literature. (1st February 2017) - Scott, Martin
Abstract : This paper presents the results of a comprehensive scoping review of empirical research into US and UK media representations of Africa published between 1990 and 2014. The results show that existing research has a remarkably narrow focus on a specific number of countries, events, media and texts. Research into representations of North Africa, Francophone Africa, non-news genres, non-elite media and radio content, is particularly scarce. This, I contend, provides an insufficient basis for reaching any firm, generalisable conclusions about the nature of media coverage of Africa. The common assumption that representations are dominated by Afro-pessimism, for example, may be accurate – but it is not currently substantiated by the existing evidence. In short, the widespread belief that we know how Africa is represented in the US and UK media is shown to be a myth. This paper also discusses how this myth has been maintained through certain citation practices and interpretations of evidence as well as the implications of these findings for the many corporations, governments, non-governmental organisations and researchers whose activities depend upon, or have helped to preserve, this myth.